Shale gas operator violations in the Marcellus and what they tell us about water resource risks. (July 2015) - Rahm, Brian G.; Vedachalam, Sridhar; Bertoia, Lara R.; Mehta, Dhaval; Vanka, Veeravenkata Sandeep; Riha, Susan J.
Abstract: Development of shale gas entails environmental risk, particularly with respect to water resources, and stakeholders are keen to assess such risks before making development decisions. We focus on Pennsylvania, USA and the Marcellus Shale, the most productive shale play in the country. We examine compliance data recorded by the state regulatory agency in order to assess environmental risks and their trends and drivers over time. Overall, we track 3267 shale gas violations, noting that environmental violation rates increase from 2007 to 2009, remain high through 2010, and then drop in 2011 and thereafter. Violations related to spills and erosion were most commonly issued. A single change in policy resulted in a 45% decrease in environmental violation rates. Furthermore, for every 1% increase in wells drilled per inspections conducted, there was a 0.56% decrease in environmental violation rates. Similar effects were not found for administrative violations. Operator identity, price of gas, and other major policies were not significantly correlated with violation rates. In comparing conventional and shale gas extraction compliance we found that shale gas development entails more risk related to spills and solid waste management, while conventional development entails more risk associated with cementing and casing issues, and site restoration. Highlights: We examine trends in violations issued to natural gas operators over 6.5 years. Analyzed 3267 unconventional and 9784 conventional violations. Decreased unconventional violation rates after 2011. Decrease best explained by shifting regulatory policy and inspector productivity. Differences in risks associated with conventional and unconventional development.